Software Artifacts based Change Controller - Agrawal, Tarun Kumar (My University, 2008)
Change is the law of nature. Software industry is not also an exception. Today software industry is facing a problem of changes in the software due to adaptation, versioning, variants, maintenance, bugs. Changes are to be made in software due to various reasons. The reasons include change of requirements, missing requirements, change of design, errors in coding, modification in coding, new market conditions, business growth/downsizing, budgetary or scheduling constraints. Modules of software may be low or high coupled. Modules of a software may also be low or high cohesive. Whenever one error occurs in one module, it can lead errors in same module as well as in other modules. As a change is made in some artifact of the software, the change will induce errors in other software artifacts. Thus a change in an artifact induces side-effectsin the software. Software developers have to put a lot of effort to find out the affected software artifacts due to a change in one artifact. Thus the development cost of software and time to develop software increases. There are a number of tools available that find the affect of change in one code module on other code modules. The proposed method not only finds the affected code module but also other software artifacts due to change in any software artifact .The proposed method stores the software artifacts in the software repository and associates the software artifacts with each other. Whenever a change occurs in a software artifact, the proposed method finds the affected software artifacts in an efficient way. Thus the software development effort and cost reduces.
Keywords: Software Engineering, Software Change, Chgange Control